2017
DOI: 10.7150/ijbs.17920
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photodynamic Therapy Using Yellow LED-light with Concomitant Hypocrellin B on Apoptotic Signaling in Keloid Fibroblasts

Abstract: Keloid is a common and refractory disease characterized by abnormal fibroblast proliferation and excessive deposition of extracellular matrix components. Hypocrellin B (HB) is a natural perylene quinone photosensitizer. In this experiment, we studied the effects of photodynamic therapy (PDT) using yellow light from light-emitting diode (LED) combined with HB on keloid fibroblasts (KFB) in vitro. Our results showed that HB-LED PDT treatment induced significant KFB apoptosis and decreased KFB cell viability. HB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Some of the preceding studies suggest that PDT induces apoptotic cell death. 20,2225 By contrast, the study by Liu et al 21 suggests that PDT may induce autophagic cell death that is dependent on superoxide anions. Thus, when cultured fibroblasts isolated from the excised keloids of six patients were treated with ALA-PDT, the fibroblasts died.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the preceding studies suggest that PDT induces apoptotic cell death. 20,2225 By contrast, the study by Liu et al 21 suggests that PDT may induce autophagic cell death that is dependent on superoxide anions. Thus, when cultured fibroblasts isolated from the excised keloids of six patients were treated with ALA-PDT, the fibroblasts died.…”
Section: Resultsmentioning
confidence: 99%
“…Several in vitro studies have also examined the effect on keloid fibroblasts of PDT employing new photosensitisers. Hu et al 24 found that PDT with the natural perylenequinone photosensitiser hypocrellin B and yellow light significantly reduced keloid fibroblast viability by inducing apoptosis (as shown by upregulated BAX expression and caspase-3 activation and downregulated BCL-2 expression). Moreover, Zheng et al 25 explored the role of RUNX3 in the response of keloid fibroblasts to pheophorbide a-based PDT (Pa-PDT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary antibodies were conjugated to either FITC or Dylight 549 for 1 h and the nucleus was counterstained with DAPI. Furthermore, Bcl‐2 and Bax protein expression was examined using flow cytometry intracellular staining as previously described …”
Section: Methodsmentioning
confidence: 99%
“…In contrast to many other PDT for deep-seated tumors, PDT for skin lesions do not restrict to limited well-penetrated near-infrared light. Studies reported that yellow LED-light, blue of argon lasers and other invisible light sources were chosen for superficial lesions, not confined to abnormal scar in PDT, and resulting in good therapeutic effects ( Hu et al, 2017 ; Tosa and Ogawa, 2020 ). Furthermore, because of less painful, more convenient, daylight photodynamic therapy (dPDT) by using sunlight as a light source became an effective alternative therapy for many superficial skin lesions ( Lee C. N et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%